Full resistance to tobacco mosaic virus infection conferred by the transgenic expression of a recombinant antibody in tobacco - (:unkn) unknown (DIAGNOSIS PRESS LTD, 2001)
The objective of this study was to obtain transgenic tobacco (Nicotiana tabacum L. cv. Samsun NN) plants resistant to tobacco mosaic virus, TMV-vulgare strain, by the expression of a single-chain variable fragment (scFv-anti-TMV) against the TMV coat protein. The scFv-anti-TMV gene was made by combining the coding sequences of the heavy and light chain variable domains of the full antibody molecule with a sequence encoding a flexible linker. The scFv-anti-TMV was cloned under the control of the 35S promoter in the plant expression vector pBI121, and used for Agrobcterhan-mediated transformation of tobacco. Integration of the scFv-anti-TMV gene into the genome of the transgenic plants and its expression were confirmed using PCR, immunoblot, and ELISA analysis. Transgenic plants expressing scFv-anti-TMV and untransformed control plants transformed with pBI121 only were inoculated with 1 mug/ml TMV. Constitutive expression of this scFv-anti-TMV resulted in complete immunity against TMV infection in transgenic plants (100% reduction of virus infection). In contrast, control plants were heavily infected by TMV. These results confirmed the applicability of antibody expression as a means of protecting plants from virus infection.
Keywords: CHAIN FV-ANTIBODY; NICOTIANA-TABACUM; ESCHERICHIA-COLI; PROTEIN; PLANTS; BINDING; CLONING; DNA